CLASSROOM OBSERVATION- A POWERFUL TOOL FOR CONTINUOUS PROFESSIONAL DEVELOPMENT (CPD) - Shanjida Halim; Rizwana Abdul Wahid; Tanzina Halim (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
For making teaching and learning more visible, classroom observation plays a central role. It provides teachers with constructive critical feedback in order to improve their classroom management and instructional techniques. For teachers it is important to observe the interaction between teacher-learner within the classroom because it can determine the learning opportunities that students get. Not only that, classroom observation encourages colleagues to collaborate to improve teacher practice and student learning. Feedback from classroom observations is an effective way for providing teachers with the information they need about their classroom behavior, and it can help them in their continuous professional development (CPD). This paper is based upon a practical approach to professional development among teachers through classroom observation. Since we, as teachers, are not born with innate teaching abilities, in fact, we learn and develop gradually with the help of some practical approaches, and classroom observation is a well-known powerful practical approach in primary and higher education to help teachers improve their teaching quality. This article mainly highlights the importance of classroom observation and its guidelines adapted from Observing Classes-CETaL. Further, it emphasizes the limitations of classroom observation, and suggests the ways to carry it out effectively based upon Observing Classes CETaL Model.